1996
DOI: 10.1111/j.1439-0523.1996.tb00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of tocopherol composition in sunflower seeds as a basis of breeding for improved oil quality

Abstract: The variabihty of seed tocopherol content in wild sunflower species, the expressivity of tph\ and tph2 mutations in different lines and the oxidative stability of sunflower oil with altered tocopherol and fatty acid composition were objectives of this research.Near-isogenic lines for three genes, i.e. Tphl, Tphl, and 01, were developed and investigated. Tocopherol content was determined with TLC and HPLC, as well as fatty acid composition with GC of methyl esters. Rancimat tests were used to estimate the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(142 citation statements)
references
References 10 publications
12
128
0
2
Order By: Relevance
“…This finding could explain why Zheshuang 72 seeds had higher T-Toc content, because γ-Toc is the predominant isomer in B. napus seeds. These findings are consistent with those of Tan (1989) and Demurin et al (1996) who reported the predominance of γ-Toc in B. napus seeds. Toc composition is defined in terms of the α-/γ-Toc ratio, an important index used to measure seed quality.…”
Section: Variation In Toc Contents Of the Five Genotypessupporting
confidence: 83%
“…This finding could explain why Zheshuang 72 seeds had higher T-Toc content, because γ-Toc is the predominant isomer in B. napus seeds. These findings are consistent with those of Tan (1989) and Demurin et al (1996) who reported the predominance of γ-Toc in B. napus seeds. Toc composition is defined in terms of the α-/γ-Toc ratio, an important index used to measure seed quality.…”
Section: Variation In Toc Contents Of the Five Genotypessupporting
confidence: 83%
“…According to Rieseberg and Ellstrand [28], only 45% of the morphological characters are intermediate, while 45% have parental dominance and 10% are transgressive. In plants, there have been several welldocumented reports that morphological markers can be problematic for the identification of hybrids because of their environmental plasticity and unknown mode of expression [29,30]. Consequently, it was important to ascertain if morphology in sunflowers is a good predictor of the status of hybrids and if it constituted a valid form of independent evidence for the identification hybrid plants.…”
Section: Discussionmentioning
confidence: 99%
“…This fact is relevant to both parental species, H. annuus and V. encelioides since they contain a number of natural antioxidants such as ascorbic acid, gluthathione, tocopherols, polyphenols such as flavonoids, etc. [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Une stabilité de l'expression des performances variétales, et une variabilité génétique suffisante pourraient rendre possible la sélection de variétés hybrides avec des teneurs en tocophérols élevées, voire de combiner cette sélection avec la production de profils modifiés, comme cela se fait déjà pour les acides gras. Des transformations stables du profil des tocophérols par mutagenèse ont d'ailleurs été récemment obtenues chez le tournesol [36,37]. Ainsi, les données collectées au cours de ces travaux permettent de montrer que les teneurs en tocophérols pourraient être augmentées par sélection variétale, et peut-être aussi en veillant à la conduite culturale.…”
Section: Discussionunclassified
“…Ainsi les températures élevées [34,35] ou le déficit hydrique [35] ont une influence négative sur la teneur de l'akène en tocophérols. Concernant le tournesol, la teneur totale et la composition en tocophé-rols est influencée par le génotype [27,[36][37][38] et par les effets environnementaux (lieu de culture) [30]. Toutefois, à notre connaissance aucune étude n'a été entreprise afin d'établir et de compléter les cinétiques de remplissage des akènes en tocophérols à l'aide de plusieurs génotypes et années de culture.…”
Section: Introductionunclassified